Use of immunological methods in the study of the wine proteins - Monteiro, S. (2013)
Monteiro et al. (1999) produced antibodies against the total proteins and against individual polypeptides from a Portuguese wine. In the present work this antibodies were used to detect the presence of identical or similar proteins in distinct wines or in wines prepared from diferent grape varieties.